2019
DOI: 10.1103/physrevphyseducres.15.020139
|View full text |Cite|
|
Sign up to set email alerts
|

Probing student reasoning in relating relative phase and quantum phenomena

Abstract: In quantum mechanics, probability amplitudes are complex numbers and the relative phases between the terms in superposition states have measurable effects. This article describes an investigation into sophomore-and junior-level students' reasoning patterns in relating relative phases and real-world quantum phenomena. The investigation involved one observational experiment and three testing experiments, during which we formulated and tested three hypotheses that allow us to gain insights into why students have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The 'conceptual change' perspective allowed us to highlight that students' conceptual difficulties in QP originate in a deeply rooted conceptual framework that is stable over time and resistant to change and QP education should aim to restructure students' conceptual frameworks (e.g., Ayene et al, 2019;Kalkanis et al, 2003;Oh, 2011). The 'mental models' perspective can illustrate that students' prior ideas are not elaborated or stable, and students' reasoning can depend on the physical context as well as on the framing of the problem (Didiş et al, 2014;Hubber, 2006;Wan et al, 2019). Conceptual difficulties surface as students struggle to make meaning, and their reasoning is based on the inappropriate activation of contextdependent cognitive or meta-cognitive resources.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The 'conceptual change' perspective allowed us to highlight that students' conceptual difficulties in QP originate in a deeply rooted conceptual framework that is stable over time and resistant to change and QP education should aim to restructure students' conceptual frameworks (e.g., Ayene et al, 2019;Kalkanis et al, 2003;Oh, 2011). The 'mental models' perspective can illustrate that students' prior ideas are not elaborated or stable, and students' reasoning can depend on the physical context as well as on the framing of the problem (Didiş et al, 2014;Hubber, 2006;Wan et al, 2019). Conceptual difficulties surface as students struggle to make meaning, and their reasoning is based on the inappropriate activation of contextdependent cognitive or meta-cognitive resources.…”
Section: Discussionmentioning
confidence: 99%
“…Students' meaning-making process is at the centre of students' conceptual difficulties when learning QP (e.g., Modir et al, 2019;Wan et al, 2019). Students learning QP construct knowledge for themselves where their prior ideas serve as both a foundation and building material for constructing new (i.e.…”
Section: Conceptual Difficulties: a Learning Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…In 2006, Singh [5] discussed specific student difficulties in quantum mechanics of particular relevance to quantum computing applications. Though explicit references to quantum information science are otherwise sparse in the literature, a number of subsequent publications have elucidated additional student difficulties relevant to QIS education [6][7][8][9][10]. Notably for our context, Passante et al [6] found that more than half of surveyed undergraduate and beginning graduate students failed to distinguish between an ensemble of particles in a superposition state (in this case,…”
Section: Background and Theoretical Frameworkmentioning
confidence: 93%